Aturan Non Fungible Token (NFT) dalam Hukum di Indonesia - Muhammad Alief Bayu Syahputra; Rahandy Rizki Prananda (UNES Law Review, 2023)
Crypto assets, especially non-fungal tokens (NFT), have now become a trend for the public to be traded. This brings a lot of influence, both the acquisition of large profitability by business people and the large losses from these business people. Regulations related to NFTs are still very limited which has led to the development of perspectives to regulate NFTs in a comprehensive manner. The study that will be carried out is a type of normative law through the study of literature and other legal materials, for example principles, rules and also legal norms. The results of the study show that there are no specific rules regarding unified NFTs, they cannot be used as the main motive for making new regulations related to NFTs. This is because new drafting rules cannot provide a clear solution for every problem and can sometimes be detrimental to NFT practices which tend to be dynamic. This can arise if regulatory arrangements are not based on a philosophical, economic, juridical or sociological basis.